Working Environment Design for Effective Palletizing with a 6-DOF Manipulator. (13th April 2016) - Chiba, Ryosuke; Arai, Tamio; Ueyama, Tsuyoshi; Ogata, Taiki; Ota, Jun
Palletizing is an important and fundamental task for production. We propose a design method to improve the performance of a palletizing manipulator. The working environment must be optimized regarding the base position of the manipulator and the shape and position of the pallet. Designing a working environment is a lengthy process because of the many dimensions of the problem and the necessity of collision-free path planning. To reduce the computation time, the parameters of an environment are quickly evaluated with the proposed method, in which we set passing points to reduce the computation time of path planning. We verify the effectiveness of our method compared with conventional and state–time space methods. We show that the proposed method can obtain effective and convenient solutions when compared to the other methods.